Foundational Issues in Educating Young People for Understanding and Appreciation of the Religions in Their Communities - Engebretson, Kathleen (Catholic Education: A Journal of Inquiry and Practice, 2012)
This is a conceptual paper considering some of the foundational issues that a teacher needs to have at least considered (if not resolved) when he or she sets out to encourage students to understand and appreciate the variety of religions in their communities. The first issue is that of what to call the enterprise; the second relates to assumed hierarchies of religions and the barriers these can impose on genuine education about religions; the third issue is that of the fundamentalist student; the fourth issue is the pervasive presence of religious history especially when religion has been the oppressor; the fifth, the position of the believing student in the conversation; and the sixth, the development of critical thinking about religions. All of these foundational issues provide rich content for educators’ reflections, reading, and discussions with colleagues and dialogue with students.